Strengthening Pancasila Ideology in Fortifying Moral Behavior among Students - Ashika Ruth Laura Sirait; Kania Salsabilah Daulay; Nur Akhillah; Mutiara; Shofiyah; Jamaludin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Numerous significant changes in social, economic, political, and even educational spheres have emerged from the reform era. After the crisis struck and sparked a recession, Pancasila started to change. As a result, Pancasila education is necessary to transmit Pancasila ideals from generation to generation. The degree of pupils' knowledge and comprehension of Pancasila doctrine is the issue at hand. How might the Pancasila attitude among students be strengthened? Pancasila is significant not only as a way of life but also as the basis of the nation and its identity. Pancasila serves as a state ideology and occasionally faces a number of difficulties. in order to preserve Pancasila's status as the official state philosophy.